The Readability Level of Arabic Textbook “Silsilah Fī Ta’līm al-Lughah al-‘Arabiyyah” - Puti Zulharby; Ahmad Marzuq; Aziz Ritonga (IAIN Salatiga, 2021)
The purpose of this study was to know the readability level of textbook